Feedlot performance and carcass characteristics of Sudan Desert sheep raised under irrigated Gezira conditions - Suliman, A.H.; El-Amin, F.M. (1980)
Feedlot performance and carcass quality were investigated on Sudan Desert sheep raised under irrigated conditions in the Gezira area. Average daily gain over the fattening period of 56 days in the feedlot was 237.0±2.0 g. Single born lambs grew faster than twin-born lambs (p